(untitled) (Revista Tópos, 2013)
Este trabalho apresenta discussões sobre planejamento regional, no âmbito da Comissão Interestadual da Bacia Paraná Uruguai – CIBPU e a elaboração do Projeto do Distrito Industrial para a o município de Presidente Prudente. Este Projeto foi o resultado de uma proposta de desenvolvimento regional, com base no binômio urbanização e industrialização como requisitos para o desenvolvimento econômico das cidades brasileiras nas décadas de 60 e 70. O trabalho intitulado “Projeto de um Distrito Industrial – Presidente Prudente”, desenvolvido entre os anos de 1966-1968 pelo Centro de Pesquisas e Estudo Urbanísticos da Faculdade de Arquitetura e Urbanismo da Universidade de São Paulo (CEPEU-FAU), em conjunto com a Comissão Interestadual da Bacia Paraná-Uruguai (CIBPU), possui um papel importante na historiografia urbana brasileira, tanto pela escala e abrangência dentro do planejamento regional, como pelas teorias urbanísticas e metodologia propostas para o desenvolvimento urbano. Palavras Chaves: Planejamento Regional, urbanização, industrialização THE ACTING OF THE INTERSTATE COMMISSION OF WATERSHED PARANÁ- URUGUAI IN PRESIDENTE PRUDENTE Abstract This paper presents discussions about regional planning, in the area of the The Interstate Commission of the Paraná-Uruguay Basin (CIBPU) and the elaboration of an Industrial District Project for the city of Presidente Prudente. This project was a result of a proposition for regional development, based on urbanization and industrialization as preconditions for economic development of Brazil’s cities in the 60’s and 70’s. The paper entitled "Design of an Industrial District - Presidente Prudente," developed between the years 1966-1968 by the Centre for Research and Urban Studies, Faculty of Architecture and Urbanism, University of São Paulo (FAU-CEPEU), together with the Interstate Commission of the Paraná-Uruguay Basin (CIBPU) has an important role in urban Brazilian historiography, both the scale and scope within the regional planning and urban theories and methods proposed for urban development. Keywords: Regional Planning, urbanization, industrialization.